2008
DOI: 10.1002/mnfr.200700393
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds: Evidence for inhibitory effects against obesity and their underlying molecular signaling mechanisms

Abstract: Phenolic compounds are widely present in the plant kingdom. Many epidemiological studies have indicated that consumption of some plant-derived foodstuffs with high phenolic content is associated with the prevention of some diseases and that these compounds may have similar properties to antioxidants, antimutagenic agents, antithrombotic agents, anti-inflammatory agents, anti-HIV-1, and anticancer agents. However, obesity is an important topic in the world of public health and preventive medicine. Relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(104 citation statements)
references
References 109 publications
1
97
0
2
Order By: Relevance
“…The coumarin, esculetin, from Fraxinus rhynchophylla is reported to be active in inhibiting early stage adipogenic differentiation thereby being useful in obesity management (Shin et al, 2010) and in preventing HFD-induced hepatic steatosis (Um et al, 2013). Naturally occurring flavonoids and phenols inhibit adipogenesis in vitro (Hsu and Yen, 2007) and have inhibitory effects on obesity (Hsu and Yen, 2008). Flaxseed lignans have been reported to show beneficial effects on lipid metabolism in diet-induced obesity in mice (Fukumitsu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The coumarin, esculetin, from Fraxinus rhynchophylla is reported to be active in inhibiting early stage adipogenic differentiation thereby being useful in obesity management (Shin et al, 2010) and in preventing HFD-induced hepatic steatosis (Um et al, 2013). Naturally occurring flavonoids and phenols inhibit adipogenesis in vitro (Hsu and Yen, 2007) and have inhibitory effects on obesity (Hsu and Yen, 2008). Flaxseed lignans have been reported to show beneficial effects on lipid metabolism in diet-induced obesity in mice (Fukumitsu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds are widely present in the plant kingdom, and evidence for phenolic compounds having a beneficial effect in fighting obesity is increasingly being reported in scientific literature. 20) Boschoff 21) has discussed quercetin as a candidate for preventing obesity-related diseases. The antioxidative activity of phenolic acids has been reported to be associated with the induction of apoptosis, 2) the inhibitory effect on proliferation, 22) and the inhibition of adipogenesis in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…(95,96) However, the extent of these health beneficial effects is unclear since only limited clinical research has been reported. Reduction in oxidative stress is implicated in these protective processes, (97) therefore sorghum polyphenolic compounds may be relevant in disrupting the cascade of pathophysiological changes that lead to metabolic disease.…”
Section: Phenolic Compoundsmentioning
confidence: 99%